2001
DOI: 10.1016/s0896-6273(01)00413-5
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Roles of Olig2 and Neurogenin2 in the Coordinated Induction of Pan-Neuronal and Subtype-Specific Properties of Motoneurons

Abstract: Distinct classes of neurons are generated at defined times and positions during development of the nervous system. It remains elusive how specification of neuronal identity coordinates with acquisition of pan-neuronal properties. Here we show that basic helix-loop-helix (bHLH) transcription factors Olig2 and Neurogenin2 (Ngn2) play vital roles in the coordinated induction of pan-neuronal and subtype-specific properties of motoneurons. Olig2 and Ngn2 are specifically coexpressed in motoneuron progenitors. Misex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
346
2
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(375 citation statements)
references
References 57 publications
23
346
2
4
Order By: Relevance
“…Olig2 is a bHLH transcriptional repressor protein that plays essential roles in the lineage specification of progenitor cells into neuronal subtypes (somatic motor neurons and forebrain cholinergic neurons) and oligodendrocytes during central nervous system development [60][61][62][63][64][65][66]. At early embryonic stages, one key role of Olig2 is to maintain progenitor cells in a replication-competent state [67].…”
Section: Discussionmentioning
confidence: 99%
“…Olig2 is a bHLH transcriptional repressor protein that plays essential roles in the lineage specification of progenitor cells into neuronal subtypes (somatic motor neurons and forebrain cholinergic neurons) and oligodendrocytes during central nervous system development [60][61][62][63][64][65][66]. At early embryonic stages, one key role of Olig2 is to maintain progenitor cells in a replication-competent state [67].…”
Section: Discussionmentioning
confidence: 99%
“…In both chicks and mice, the p3 and pMN populations of ventral spinal cord precursor cells express Nkx2.2 and Olig2, respectively, through the period of motor neuron development (Mizuguchi et al, 2001;Novitch et al, 2001;Soula et al, 2001;Sun et al, 2001;Zhou et al, 2001;Fu et al, 2002). In chick embryos, Nkx2.2 + cells then begin to disperse throughout the spinal cord in a pattern characteristic of OPCs (Xu et al, 2000).…”
Section: Discussion Opcs Arise From Nkx22a + and Nkx22a − Spinal Comentioning
confidence: 99%
“…In chick embryos, Nkx2.2 + cells then begin to disperse throughout the spinal cord in a pattern characteristic of OPCs (Xu et al, 2000). At about the same time, Nkx2.2 expression expands dorsally into the Olig2 expression domain (Mizuguchi et al, 2001;Novitch et al, 2001;Sun et al, 2001;Zhou et al, 2001;Fu et al, 2002). Double labeling experiments showed that Nkx2.2 + dispersing cells initially are both Olig2 + and Olig2 − but that later, most cells in the spinal cord white matter are Nkx2.2 + Olig2 + (Zhou et al, 2001;Fu et al, 2002).…”
Section: Discussion Opcs Arise From Nkx22a + and Nkx22a − Spinal Comentioning
confidence: 99%
“…The most likely explanation of this interesting pattern is that overexpression of proneural genes may induce neural progenitor differentiation and promote their migration from the medial to the lateral half [50]. However, 20% of cells with similar amounts of bHLH protein expression did stay in the medial half (arrow in Figure 5C-D and data not shown); this was probably owing to the different intracellular competence between these cells and the migrating cells.…”
Section: Discussionmentioning
confidence: 94%